1995
DOI: 10.1007/bf00151036
|View full text |Cite
|
Sign up to set email alerts
|

Improved early bone-implant integration in transgenic mice overexpressing bovine growth hormone

Abstract: Titanium implants were inserted in transgenic mice overexpressing bovine growth hormone. Four weeks after insertion the implants were cut out en blocwith the surrounding bone. The undecalcified specimens were cut and ground to a thickness of approximately 10 I~m. Histomorphometry demonstrated significantly more direct bone to metal contact for the transgenic mice than for the non-transgenic littermates. The results indicate that endogenous high levels of bovine growth hormone result in improved early bone-impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Second, it will allow for cost effective screening of potential countermeasures for impaired osseointegration prior to testing in larger animals. Two laboratories reported preliminary osseointegration studies in mice in the mid-1990s [51,52,53]. Recently, osseointegration studies in mice have demonstrated that molecular pathways known to regulate bone turnover also affect osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it will allow for cost effective screening of potential countermeasures for impaired osseointegration prior to testing in larger animals. Two laboratories reported preliminary osseointegration studies in mice in the mid-1990s [51,52,53]. Recently, osseointegration studies in mice have demonstrated that molecular pathways known to regulate bone turnover also affect osseointegration.…”
Section: Discussionmentioning
confidence: 99%